2021
DOI: 10.5454/mi.15.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Potential Zoonotic Faecal Bacteria from Sunda Porcupine (Hystrix javanica ) and Their Antimicrobial Resistance Profiles

Abstract: Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus (DENV) which spread widely in tropical and subtropical regions of the world. DENV is a single-positive strand RNA virus with a genome size of ± 11kb which encodes three structural proteins, seven non-structural proteins, and two untranslated regions (UTR). The non-structural protein-1 (NS1) of DENV is known to have important role in dengue pathogenesis also promising to be developed as dengue vaccine. Lately, novel v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The genus Salmonella contains several species that can cause food borne gastrointestinal diseases [27]. Our study strengthens the result of the previous study [11,21], that Sunda porcupine is a natural reservoir of Salmonella. The bacteria also can be found in poultry, pigs, cattle, birds, reptiles, rodents and companion animals [28].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The genus Salmonella contains several species that can cause food borne gastrointestinal diseases [27]. Our study strengthens the result of the previous study [11,21], that Sunda porcupine is a natural reservoir of Salmonella. The bacteria also can be found in poultry, pigs, cattle, birds, reptiles, rodents and companion animals [28].…”
Section: Resultssupporting
confidence: 89%
“…The previous report on fecal pathogenic bacteria in Sunda porcupine using culture and followed by 16s rRNA sequence analysis approaches, found that Salmonella spp., Listeria spp., Proteus mirabilis, Shigella flexneri and Klebsiella quasipneumoniae subsp. similipneumoniae were inhabiting the feces [11]. Salmonella was also found on the dorsal skin of Sunda porcupine [21].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Several reports showed that gastrointestinal diseases occur in porcupines, such as bacterial infections, including Proteus mirabilis and Shigella flexneri. It can also be affected by parasite infection, such as Giardiasis, Cryptosporidiosis, Echinococcus ortleppi, Linguatula serrata, Trichuris sp, and Gireterakis girardi (Nugroho and Purwaningsih 2015;Rajabloo et al 2015;Hodžić et al 2018;Coppola et al 2020;Cavallero et al 2021;Nisa et al 2021). In order to support the captive breeding activity of the Sunda porcupine, the study of the digestive system is required.…”
Section: Introductionmentioning
confidence: 99%